G-C3N4 supported metal (Pd, Ag, Pt) catalysts for hydrogen-production from formic acid. (10th May 2018) - Liu, Xiaotong; Su, Penghe; Chen, Ya; Zhu, Baolin; Zhang, Shoumin; Huang, Weiping
Abstract : Pd/g-C3 N4 with d–π interaction between Pd NPs and g-C3 N4 with a π-conjugated system shows high catalytic activity in the dehydrogenation of FA. Abstract : g-C3 N4 supported metal (Pd, Ag, Pt) catalysts were synthesized, and their catalytic performances for hydrogen-production from formic acid were evaluated. The Pd catalyst can effectively turn formic acid into H2 and CO2 with 100% selectivity at room temperature or even at a lower temperature. The catalysts were characterized with TEM, XPS, PXRD, ICP, Chemisorption, IR spectra and Raman spectra. The results indicate that the good catalytic performance of the catalysts could be attributed to the interaction between g-C3 N4 and the metal nanoparticles: that is, the overlap between the d-orbitals of Pd and the π-conjugated system of g-C3 N4 . The effect of the interaction was verified by analyzing the contrasting catalytic performances of Pd/g-C3 N4, Ag–Pd/g-C3 N4, Pt–Pd/g-C3 N4 and Pd/HTNTs (hydrogen titanate nanotubes) for hydrogen-production from formic acid.